Unveiling dynamic connectedness: how macroeconomic variables drive consumer and business confidence - Polat, Onur; Ertugrul, Hasan Murat; Arzova, Sabri Burak; Sahin, Bertac Sakir (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThe study aims to explore the key determinants of consumer and business confidence by analyzing the interconnectedness between macroeconomic factors and economic sentiment.Design/methodology/approachThis study employs a time-varying parameter vector autoregression (TVP-VAR) asymmetric connectedness model to analyze the dynamic relationship between macroeconomic variables and economic confidence in the United States from 1994 to 2023. The model examines consumer and business confidence indices about U.S. Treasury maturity, the Federal Fund Rate, geopolitical risk, Moody's Seasoned AAA Corporate Bond Yield, short-term interest rates and oil and gas prices.FindingsEmpirical results indicate that negative return spillovers dominate economic confidence transmission, particularly during economic and geopolitical uncertainty periods. The federal fund rate and short-term interest rates are identified as the most significant transmitters of spillovers. The study also finds that oil and gas price fluctuations impact economic sentiment asymmetrically, with stronger effects during financial crises.Originality/valueThis study contributes to the literature by adopting a novel connectedness approach to examine the dynamic interplay between variables. By incorporating both consumer and business confidence indices, it provides a comprehensive perspective on economic sentiment transmission. Furthermore, including asymmetric spillover effects distinguishes this research from existing studies, offering valuable policy insights for managing economic confidence during periods of uncertainty.
Keywords: Economic confidence; Energy prices; Geopolitical risks; Treasury maturity; Corporate bond yield; US; C32; C51; E43; G15; OIL; PRICES; SHOCKS; Business & Economics